The effectiveness of vitamin C supplements in pregnant women toward premature rupture of membranes - Dartiwen, D; Nurmala, Cucu (Universitas Aisyah Pringsewu, 2020)
Premature Rupture Of Membranes (PROM) is a problem related to maternal death caused by infection. In Indonesia, it is estimated that every year 20-30 percent of women experience PROM. One way to prevent PROM is by giving vitamin C. The purpose of this study is to uncover new things, namely the effectiveness of supplement vitamin C in pregnant women, to prevent the occurrence of PROM. This research is quasi-experimental. The study population was all pregnant women with predisposing factors. The sample in this study, most pregnant women, aged 20 weeks with predisposing factors of PROM who met the inclusion and exclusion criteria were 200 pregnant women, consisting of 100 pregnant women in the experimental group and 100 pregnant women in the control group. Data processing uses univariate, bivariate, and multivariate analysis. Data collection is done by observation at the time of delivery. The results of the study of 100 pregnant women in the experimental group were 6 percent who experienced PROM after consuming vitamin C while out of 100 pregnant women in the control group who experienced PROM as much as 56 percent. The results of the study prove that the provision of vitamin C in pregnant women is effective in preventing the incidence of premature rupture of membranes (OR = 13,184). This study concludes that to prevent the occurrence of premature rupture of the membranes it is recommended that pregnant women starting at gestational age 20 weeks consume vitamin C 100 mg/day. Efektivitas pemberian suplemen vitamin C pada ibu hamil terhadap kejadian ketuban pecah diniAbstrakKetuban Pecah Dini (KPD) merupakan suatu masalah yang berhubungan dengan kematian ibu yang disebabkan oleh infeksi. Tujuan penelitian ini mengungkap hal baru yaitu efektivitas pemberian suplemen Vitamin C pada ibu hamil untuk mencegah terjadinya PROM. Penelitian ini merupakan penelitian quasi eksperimen. Populasi penelitian adalah semua ibu hamil dengan faktor predisposisi. Sampel dalam penelitian, sebagian ibu hamil usia kehamilan 20 minggu dengan faktor predisposisi PROM yang memenuhi kriteria inklusi dan eksklusi sebanyak 200 ibu hamil, yang terdiri dari 100 ibu hamil kelompok eksperimen dan 100 ibu hamil kelompok kontrol. Pengolahan data menggunakan analisis univariat, bivariat dan multivariat. Pengumpulan data dilakukan dengan observasi pada saat persalinan. Hasil penelitian dari 100 ibu hamil pada kelompok eksperimen sebanyak 6 persen yang mengalami PROM setelah mengkonsumsi vitamin C sedangkan dari 100 ibu hamil pada kelompok kontrol yang mengalami PROM sebanyak 56 persen. Hasil penelitian membuktikan bahwa pemberian vitamin C pada ibu hamil efektif untuk mencegah kejadian Ketuban Pecah Dini (OR=13,184). Penelitian ini menyimpulkan bahwa untuk mencegah kejadian ketuban pecah dini disarankan ibu hamil mulai usia kehamilan 20 minggu mengkonsumsi vitamin C 100 mg/hari.